SOCIALHEALm PROMOTION: HARMFUL HEALm PRACI1CFS: Being a text of Lead paper presented at the 8th National Conference! Workshop of the Health Promotion Research Association of Nigeria (HEPRAN) at the University of Nigeria, Nsukka. - Musa, Danladi (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
cial health is a component of the general health status that has been neglected or ’c underrated compared to other dimensions of health. A look at the health education curricular of our tertiary institutions shows that only little provision is made for social health. Yet, it is common knowledge that the health problems generated from human behaviour (i.e. what we do or what we fail to do) far outweighs those arising from pathogenic health problems these days. When one thinks of the health risks of prostitution, the health problems emanatingfrom neglected orphans and vulnerable children or poor interpersonal relationships, one has no option but to appreciate the importance of good social health.